2017
DOI: 10.1122/1.4998159
|View full text |Cite
|
Sign up to set email alerts
|

The microscopic origin of the rheology in supramolecular entangled polymer networks

Abstract: Supramolecular groups in polymeric systems lead to responsive materials which are ideally suited for applications in dynamic environments. The key to their advanced properties such as shape-memory or self-healing is the reversibility of secondary interactions which can be triggered by external stimuli such as temperature, light, or pH-value. Controlling the (mechanical) behavior of such systems requires a precise understanding of intrinsic properties. We present a multimethod study of transient polyisoprene ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 68 publications
3
34
0
Order By: Relevance
“…45 In fact, in nearly monodisperse polymers with stickers randomly distributed along the chain the shallowing was still observed. 43,44 In another study, on the contrary, with Đ of nearly 2 with each repeating unit carrying a sticker, no shallowing was observed (Figure 10). 77 It might be tempting to conclude that the sticker distribution is rather the important parameter, but in another study on monodisperse polymers with randomly located stickers slopes of 1 and 2 were observed.…”
Section: Sticker Positionmentioning
confidence: 87%
“…45 In fact, in nearly monodisperse polymers with stickers randomly distributed along the chain the shallowing was still observed. 43,44 In another study, on the contrary, with Đ of nearly 2 with each repeating unit carrying a sticker, no shallowing was observed (Figure 10). 77 It might be tempting to conclude that the sticker distribution is rather the important parameter, but in another study on monodisperse polymers with randomly located stickers slopes of 1 and 2 were observed.…”
Section: Sticker Positionmentioning
confidence: 87%
“…The obtained information on local dynamics may provide insights into the microscopic mechanisms governing the viscoelastic response of the investigated systems. Importantly, for associative systems, or even for concentrated solutions in complex solvents such as ionic liquids, it is unclear whether application of time-temperature superposition is appropriate even if a master curve can be obtained, since interpretation of the shift factors is complicated (Gold et al 2017;Zhang et al 2018). Independent high-frequency measurements can be very valuable in this regard.…”
Section: Applicationsmentioning
confidence: 99%
“…The effect of UPy addition on the linear viscoelasticity of supramolecular polymers has previously been investigated [20,[63][64][65][66]. However, few studies exist where the rheological response is characterised for a systematic variation of supramolecular side-group density [41,66,67].…”
Section: Introductionmentioning
confidence: 99%